Elections In Determining Regional Leadership With Integrity - Hakim, Setiawandi (Future Science, 2025)
In addition to the election of members of the representative council, in 2024 there will also be an election for the leaders of the government, both central and regional, namely the election of the President and Vice President, the Election of Governors and the Election of Regents/Mayors. The 2024 Regional Head Election must produce regional leaders with integrity. Research Method: Literature study with a qualitative descriptive model is used in this writing to describe the answers to the problem of regional head elections, where currently many regional heads do not have integrity. Conclusion: 1. Government institutions such as the Corruption Eradication Committee (KPK) and other institutions related to the eradication of corruption carry out prevention and law enforcement efforts effectively, in a targeted, planned and massive manner. 2. Increase the role of universities through levies on the implementation of the tridharma of higher education which are directed at creating public understanding of the importance of leaders with integrity. 3. Increase community participation which is preceded by a change in people's thinking patterns in creating leaders with integrity, which is carried out in the following ways: a. Do not make regional head elections a field for seeking income through methods that are contrary to morals and rules. b. Determine the choice according to a good track record that the prospective leader has integrity, insight, leadership skills and behaves simply. 4. The Role of the Region Before the Regional Election is carried out by improving the welfare of the community through the use of regional resources owned and providing an understanding to the community that the function and role of the regional head are so important in development, both physical, social and economic, so that they must choose a leader who has integrity, insight, leadership skills and behaves simply. Suggestions: 1. So that all government institutions, both those directly related and not directly related to the eradication of corruption, and Universities immediately optimize their role in creating regional leaders with integrity. 2. So that the community immediately realizes that a leader with integrity is needed, so that in the implementation or before and after the implementation of the regional head election they do not receive anything, either material or immaterial, that leads to the results of the regional head election that does not have integrity.